2021
DOI: 10.3389/fphar.2021.727874
|View full text |Cite|
|
Sign up to set email alerts
|

Sanqi Oral Solution Mitigates Proteinuria in Rat Passive Heymann Nephritis and Blocks Podocyte Apoptosis via Nrf2/HO-1 Pathway

Abstract: Idiopathic membranous nephropathy (IMN) is the most common pathological type in adult nephrotic syndrome where podocyte apoptosis was found to mediate the development of proteinuria. Sanqi oral solution (SQ), an effective Chinese herbal preparation clinically used in treatment of IMN for decades, plays an important role in reducing proteinuria, but the underlying mechanisms have not been fully elucidated yet. The current study tested the hypothesis that SQ directly lessens proteinuria in IMN by reducing podocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…A large number of studies have shown that traditional Chinese medicine and its active ingredients can effectively promote the remission of kidney disease. 18 , 19 Kidney is an important target organ for iohexol-induced cytotoxicity. Iohexol-induced AKI involves multiple pathophysiological mechanisms, including renal inflammation, pyroptosis, oxidative stress, proximal renal tubular injury, and vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that traditional Chinese medicine and its active ingredients can effectively promote the remission of kidney disease. 18 , 19 Kidney is an important target organ for iohexol-induced cytotoxicity. Iohexol-induced AKI involves multiple pathophysiological mechanisms, including renal inflammation, pyroptosis, oxidative stress, proximal renal tubular injury, and vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…As a clinical symptom of NS, proteinuria is accompanied by the onset and development of NS. Proteinuria is mainly due to the destruction of the GFB, in which podocytes play an important role ( Wang et al, 2021 ). Podocytes have free and dispersed FPs, and adjacent FP bridges to form slit diaphragm, dynamically modified by the actin cytoskeleton ( Hu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TRPC6 may be a breakthrough point in elucidating the pathogenesis of NS. Most importantly, it was recently reported that AngⅡ-stimulated podocytes can significantly increase the expression of TRPC6 ( Wang et al, 2021 ). Therefore, the AngⅡ-TRPC6 targeting pathway may be a new strategy for modern NS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous basic studies have also shown that Sanqi formula could effectively help rat model of membranous nephropathy via reducing proteinuria, increasing serum albumin, ameliorating renal damage which is associated with the suppression of nuclear factor-kappa B (NF-κB) [ 41 ]. Besides, our studies reveal that Sanqi Oral Liquid protect podocyte as evidenced by effectively reducing podocytes apoptosis which is associated with nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway [ 42 ]. Our another experimental studies based on rat model of renal ischemia/reperfusion (I/R) injury demonstrated that Sanqi Oral Liquid has a significant effect on the immune system and exerts renoprotective effects by regulating apoptosis and autophagy, which may be linked to extracellular signal-regulated kinase (ERK)/mammalian target of rapamycin (mTOR) pathways [ 43 ].…”
Section: Discussionmentioning
confidence: 99%